Additional record of Janetogalathea californiensis (Anomura: Galatheidae) from the central Gulf of California, Mexico, with notes on its distribution - Hendrickx, Michel E.; Ayón Parente, Manuel; Serrano, David (HIDROBIOLÓGICA, 2017)
Specimens of galatheids Janetogalathea californiensis (Benedict, 1902) were collected in the northern portion of the Central Gulf of California and represent the third record for this species in the area. Illustrations of the material collected in the Gulf of California are provided and some differences are noted when compared to the description of the paralectotypes. Depth range of the species is discussed and set at 87-786 m. The presence of a wide and deep Oxygen Minimum Zone in the area is believed to limit the dispersion of J. californiensis to the south and to deeper water of the gulf.